Relationship between 24-h urine sodium/potassium ratio and central aortic systolic blood pressure in hypertensive patients - Rhee, Moo-Yong; Shin, Sung-Joon; Gu, Namyi; Nah, Deuk-Young; Kim, Byong-Kyu; Hong, Kyung-Soon; Cho, Eun-Joo; Sung, Ki-Chul; Lee, Sim-Yeol; Kim, Kwang-Il (Hypertension research, 2017)
Studies evaluating the relationship between measured 24-h urine sodium (24HUNa), potassium (24HUK) and aortic blood pressure (BP) are rare, and no such study has been performed with an Asian population. We evaluated the relationship between 24HUNa, 24HUK, casual BP, 24-h ambulatory BP and aortic BP by analyzing data from 524 participants with valid 24-h urine collection, 24-h ambulatory BP and central BP measurements (mean age 48.1±9.8 years, 193 men). Hypertension was defined as a 24-h ambulatory BP ⩾130/80 mm Hg or current treatment for hypertension (n=219). The participants with hypertension and high 24HUNa (mean 210.5±52.0 mmol  per day, range 151.0-432.0) showed higher 24-h systolic (P=0.037) and diastolic BP (P=0.037) and aortic systolic BP (AoSBP, P=0.038) than the participants with hypertension and low 24HUNa (mean 115.7±25.0 mmol per day, range 45.6-150.0), adjusted for confounders. The participants with hypertension and a high ratio of 24HUNa and 24HUK (24HUNa/24HUK, mean 4.03±1.00, range 2.93-7.96) had higher AoSBP than the participants with hypertension and a low 24HUNa/24HUK ratio (mean 2.13±0.54, range 0.53-2.91), adjusted for confounders (P=0.026). The participants with hypertension demonstrated a significant linear relationship between AoSBP and 24HUNa/24HUK ratio that was independent of 24HUNa, according to the multiple regression analysis (P=0.047). In hypertensive patients, 24HUNa/24HUK was positively and more strongly related to AoSBP compared with 24HUNa alone. The result indicates that high sodium and low potassium intake may increase the subsequent risk of cardiovascular disease by elevating AoSBP.